2014
DOI: 10.1016/j.jpainsymman.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Discrimination in Health Care Is Associated With a Greater Burden of Pain in Sickle Cell Disease

Abstract: Context Perceived discriminatory experiences in society have been associated with a higher burden of pain among some minority patient populations. Objectives To describe the extent to which patients with sickle cell disease (SCD) perceive discrimination from health care providers, and to examine the association of these experiences with the burden of chronic SCD pain. Methods Cross-sectional analysis of data collected at baseline of a prospective cohort study of SCD patient experiences of care (n = 291). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 29 publications
(29 reference statements)
1
97
0
Order By: Relevance
“…This item has been used in several studies of SCD by the IMPORT research team. In a prior study, the IMPORT team demonstrated that this item performed as well as “the number of good days [the participant] experienced each week” (higher score equals a lower burden of pain during the week) and “self-reported pain on a good day” (higher score equals more severe pain on a good day) (Haywood et al, 2014), which are other items used to measure the burden of chronic pain in adults with SCD. Therefore, we selected this item as a valid measure of chronic SCD pain for the current study.…”
Section: Methodsmentioning
confidence: 99%
“…This item has been used in several studies of SCD by the IMPORT research team. In a prior study, the IMPORT team demonstrated that this item performed as well as “the number of good days [the participant] experienced each week” (higher score equals a lower burden of pain during the week) and “self-reported pain on a good day” (higher score equals more severe pain on a good day) (Haywood et al, 2014), which are other items used to measure the burden of chronic pain in adults with SCD. Therefore, we selected this item as a valid measure of chronic SCD pain for the current study.…”
Section: Methodsmentioning
confidence: 99%
“…[29][30][31] They have lower satisfaction with care, 32,33 higher levels of medical mistrust, 32 and are less likely to adhere to physicians' recommendations. 34 Thus, perceived discrimination in health care predicts a host of adverse outcomes, from poor self-reported health to obesity, diabetes, hypertension, heart disease, birth outcomes, and mental health problems. [16][17][18][19][35][36][37][38][39][40][41][42] Previous research suggests that racial discrimination may be a critical mechanism linking the aspects of racial/ethnic identity to health outcomes.…”
Section: Perceived Discrimination In Health Carementioning
confidence: 99%
“…30 (2) Patients with SCD report experiencing discriminatory behavior from health care providers. 31 (3) Higher levels of implicit bias among clinicians have been directly linked with inequities in treatment recommendations for African Americans and have been associated with poor quality of patientphysician communication. 23 (4) As a result, there can be a vicious cycle, as true or perceived discrimination from health care providers is associated with greater nonadherence to management regimens, 25 which is especially problematic for the nearly 30% of adults with SCD who report chronic pain.…”
Section: Disease Experiencementioning
confidence: 99%